SISTEM PENDUKUNG KEPUTUSAN PENYELEKSIAN KARYAWAN MELALUI PROMOSI JABATAN MENGGUNAKAN METODE PROFILE MATCHING - Wahyuni, Yuli; Koenoe, Aswin Anthon Julius (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2014)
Decision Support System becomes very important for the decision maker, especially promotion of employees. Personal assessment parameters tend to be subjective, does not result in the employee performance appraisal competency- based, so it requires the reversal of performance appraisal, the original is personal and administrative manually into computerized system. With the method of profile matching the emphasis on competence assessment is on the aspects of intellectual capacity, work attitudes and behavior of employees, while for the Visual Basic programming language using the Net in 2008 by leveragingMicrosoft SQL Server 2000 as database system. This research aims to facilitate the management in assessing, analyzing, formulating and making decisions, the results in the form of weights HR competency assessment, output of the report as supporting data and material consideration in deciding the candidate assessment Keyword: Decision Support System, promotion of employees, Profile Matching.